Paradigm shifts in recordkeeping responsibilities : implications for ISO 15489's implementation - Joseph, Pauline (2012)
Highlights the paradigm shifts that have occurred in recordkeeping responsibilities from records and information management (RIM) professionals to knowledge workers due to advancements in information and communication technologies and by user and organisational expectations.